Unlocking digital performance: exploring the mediating role of employee competitive attitudes, behaviors, and dynamic capabilities in Chinese SMEs under high-involvement human resource management practice - Wang, Guifang; Mansor, Zuraina; Leong, Yee Choy (Springer Science and Business Media Deutschland, 2024)
Digital technology has already permeated the production and operations of organizations, with many incorporating it into employee performance evaluations. However, there remains a research gap in identifying effective approaches to achieving digital performance. Furthermore, while scholars have often mentioned the differences in employee attitudes, and employee dynamic capability (EDC) in the dynamic digital market, empirical evidence supporting this notion is scarce. This paper investigates the influence of high-involvement human resource management practices (HI-HRMPs) on employee digital performance (EDP) within Chinese small and medium-sized enterprises (SMEs), focusing on specific cultural regions in China. Using purposive sampling, four representative regions (Guangzhou, Shanghai, Guizhou, and Anhui) were selected for Survey. Structural equation modeling (AMOS) was employed to examine the relationships between HI-HRMPs as the independent variable and employee competitive attitudes, employee competitive behaviors, and employee dynamic capabilities as mediating variables, with a focus on their impact on employee digital performance. Contrary to direct effects, the study reveals that HI-HRMPs do not directly influence employee digital performance. Instead, employee competitive attitudes and behaviors, along with their dynamic capabilities, emerge as significant mediating variables in this relationship. Specifically, employee competitive attitudes and behaviors, as well as employee dynamic capabilities, play crucial roles in mediating the relationship between HI-HRMPs and employee digital performance. Furthermore, the findings indicate that employee dynamic capabilities exhibit greater influence on employee digital performance compared to employee competitive attitudes and behaviors, particularly in the context of a rapidly evolving digital marketplace. These results underscore the importance of fostering employee dynamic capabilities within SMEs to enhance digital performance in the ever-changing business landscape.